’You may now speak to your lawyer’: When interpreters mediate judges’ information to the accused - Karrebaek, Martha; Kirilova, Marta; Helleshøj Sørensen , Solvej (Language and Law / Linguagem e Direito, 2023)
This paper concerns interpreter-mediated courtroom hearings in Denmark. Based on audio-recordings, we analyse the contributions of judge and interpreter, and we focus on if, how and by whom the non-Danish speaking accused is informed about the possibility to speak with a lawyer in private. Although legally trivial, this information is crucial to the accused as it concerns his/her legal rights and options. We show how the informational sequence unfolds interactionally; we argue that the work of judge and interpreter is collaborative; and we discuss the potential of our sociolinguistic / interactional perspectives to inform the legal professionals. Here we are concerned with a wide-spread understanding of quality in legal interpreting. Rather than regarding ‘quality’ as equal to ‘correct’ and ‘accurate’ translation and focusing on the work of the interpreter in isolation, we suggest that it is necessary to consider context, aims, addressees and functions of the interpreting activity. We argue that the interpreter’s work facilitates better understanding for the accused, and at the same time, a more streamlined courtroom interaction.